The enduring afterlife of Before Tomorrow: Inuit survivance and the spectral cinema of Arnait Video Productions - Chisholm, Dianne (Études/Inuit/Studies, 2016)
This essay investigates how the filmmakers of Igloolik-based women’s collective Arnait Video Productions invent and combine various techniques and strategies of spectrality and survivance to create a powerful, cinematic form of Inuit cultural resistance and resilience. I borrow the concept of “survivance” from Anishnaabe literary theorist Gerald Vizenor who uses it to explain how Aboriginal literary and linguistic traditions continue to flourish in contemporary media despite and in response to colonialism’s systemic suppression of oral traditions. With this concept I analyze the way Arnait’s films re-enact and revive Inuit culture and oral tradition in the abiding voice and spirit of the dead whose creative art of living resists extinction. Arnait has to date produced three feature films: two fictional films Before Tomorrow (2009) and Uvanga (2013), and a documentary Sol (2014). I demonstrate that all three films exhibit this uncanny mix of spectrality and survivance with focus on Arnait’s debut film as a case study.